2022
DOI: 10.1155/2022/7001743
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Study on the Correlation between the Prevalence of Venous Thromboembolism in Kazak Pregnant and Lying‐In Women in Xinjiang

Abstract: In order to reveal the correlation between the prevalence of venous thromboembolism in Kazak pregnant and lying-in women in Xinjiang, the polymorphisms in the promoter region and coding region of the TAFI gene and the interaction of environmental factors are investigated. In this study, determination and analysis of anticoagulation indexes are conducted. The activity of antithrombin III and protein C is measured by chromogenic substrate method, and the activity of protein S is measured by coagulation method. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%